Kepemimpinan Transformasional Kepala Madrasah dalam Meningkatkan Kinerja Guru Berbasis School Based Management di Raudlatul Athfal (RA) Al-Hidmah Maron Probolinggo - Husnah, Rif'atul; Qosim, Nanang; Solehudin, Sollah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study aims to investigate the transformational leadership role of madrasah heads in improving the performance of School Based Management (SBM)-based teachers in Raudlatul Athfal (RA) Al-Hidmah Maron Probolinggo. School Based Management (SBM) is considered an effective approach to improve the quality of education by giving principals and teachers authority in resource management and decision making. The focus of this research is on how the head of the as a transformational leader can have a positive impact on teacher performance through the implementation of School Based Management (SBM). The research method uses a qualitative approach with a case study in Raudlatul Athfal (RA) Al-Hidmah Maron Probolinggo which has successfully implemented transformational leadership based on school based management (SBM). Data was collected through in-depth interviews with madrasah heads, teachers, and heads of IGRA (Ikatan Guru Raudlatul Athfal)  Kecamatan Maron.  The results of research in Raudlatul Athfal (RA) Al-Hidmah Maron Probolinggo show that transformational leadership of madrasah heads has an important role in improving teacher performance. Through inspiration, motivation, and the development of a shared vision, the head of the madrasah encourages teachers to actively participate in the decision-making and implementation of School Based Management (SBM). In addition, effective communication, coaching, and self-development are also key elements of  successful transformational leadership. The implications of these findings can be used as a basis for the development of more effective education policies and leadership training in madrassas.